2009
DOI: 10.1021/ol900742p
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of 4-Amino-2,3-unsaturated-N-Cbz-imino-O-glycosides via New Diastereoisomeric N-Cbz-Imino Glycal-Derived Allyl N-Nosyl Aziridines

Abstract: The glycosylation of alcohols by the new diastereoisomeric d,l-6-deoxy-N-Cbz-imino glycal-derived allyl N-nosyl aziridines 5 and 6 affords, after deprotection of the 4-(N-nosylamino) group, the corresponding 2,3-unsaturated-N-Cbz-imino-O-glycosides bearing a free amino group on C(4) through a completely 1,4-regio- and substrate-dependent stereoselective glycosylation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
1
7
1
Order By: Relevance
“…The six-member ring arrangement stabilizes the transition state, decreases the mobility of the reaction sites, and allows for a more effective approximation of the nucleophile to the electrophile center. This result differs from the interaction of the -OH group with the nitrogen atom of the aziridine group proposed by Di Bussolo et al 1 (Scheme 2). However, the difference between the values of DG -( Table 1) of reactions of 1 and 3 for the formation of the anti-and the syn-isomers can be explained by distinct factors.…”
Section: Contents Lists Available At Sciverse Sciencedirectcontrasting
confidence: 94%
See 2 more Smart Citations
“…The six-member ring arrangement stabilizes the transition state, decreases the mobility of the reaction sites, and allows for a more effective approximation of the nucleophile to the electrophile center. This result differs from the interaction of the -OH group with the nitrogen atom of the aziridine group proposed by Di Bussolo et al 1 (Scheme 2). However, the difference between the values of DG -( Table 1) of reactions of 1 and 3 for the formation of the anti-and the syn-isomers can be explained by distinct factors.…”
Section: Contents Lists Available At Sciverse Sciencedirectcontrasting
confidence: 94%
“…This difference suggests that C1 is much more reactive than C3 upon nucleophilic addition. This explains the complete regioselectivity of the reactions of 1 and 3 and agrees with the results reported by Di Bussolo et al 1 To investigate the kinetic and thermodynamic behavior of the reactions of 1 and 3, the Gibbs free energy of activation (DG -) and of reaction (DG) were calculated; the values are provided in Table 2 (see Supplementary data for additional details). The evaluation of these values shows that in the reaction of 1, the formation of the syn-isomer is kinetically and thermodynamically favored, except in 2a, which explains the formation of only one stereoisomer in each case.…”
Section: Contents Lists Available At Sciverse Sciencedirectsupporting
confidence: 86%
See 1 more Smart Citation
“…0.2 M (Scheme ; entry 1 of Table ). , The reaction was found to occur within shorter time periods to afford 8a in excellent yields (3 h, 84%; 0.5 h, 91%: entries 2 and 3). It was also found that the reaction was completed smoothly under diluted conditions (0.02 M, 97%: entry 4).…”
mentioning
confidence: 95%
“…It has also been shown that the intramolecular alkylation of the nitrogen atom affords the cyclized product with a medium- to large-membered ring size despite the use of relatively concentrated conditions compared to the existing macrocyclization representative reactions, such as Yamaguchi’s lactonization . The cyclization reaction has indeed been applied to the total synthesis of several natural products bearing a medium-sized ring structure. , We envisaged that nosyl cyclization would be effective for the formation of winding vine-shaped molecules forming a 10-membered or higher ring size. If successful, this reaction can be an alternative protocol for achieving the generation of a new class of vine-shaped molecules.…”
mentioning
confidence: 99%